Finance and Development, March 1991. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1991)
European Community member states now face critical decisions on the design and implementation of monetary policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet